Propuesta de mejora en la productividad de la línea de vestuario en la empresa FABRIL FAME S.A. mediante un estudio de tiempos y movimientos. - Aguirre Caiza, Jessica Maribel (2019)
FABRIL FAME CORPORATION is a business with extensive experience in the market in the manufacture of clothing, footwear, and camping equipment for the Armed Forces, its production is mainly on request, after making a thorough diagnosis in the production line of clothing in the underwear product for the Ecuadorian Army it was possible to show several factors that intervene in the production process which have generated delays in the manufacturing process. The improvement in productivity in the clothes manufacturing line was made through the study of times and movements where a production bottleneck was determined which is causing a delay. A restructuring of the operations has been carried out in order to standardize the production time for each operation, taking into account the conditions, performance factors and supplements under which the operators work that will allow representing the current situation and future of the costume making line giving fulfillment to the activities proposed in each objective of the project that allows to analyze and establish opportunities for improvement. Finally, the results obtained in this project have been favorable due to the activities previously carried out with the restructuring of operations and the standardization of time, the productivity of the line has been improved by 16%; FABRIL FAME CORPORATION will optimize its administrative and human resources, being the primary beneficiaries of this proposal, and the indirect beneficiaries will be its clients because the company will be able to offer its demands in less time and with better product quality.